2021
DOI: 10.3389/fpsyg.2021.714277
|View full text |Cite
|
Sign up to set email alerts
|

People With High Autistic Traits Show Fewer Consensual Crossmodal Correspondences Between Visual Features and Tastes

Abstract: Crossmodal correspondences between visual features (e.g., color/shape) and tastes have been extensively documented in recent years. Visual colors and shapes have been shown to consensually match to specific tastes. Meanwhile, individuals with autism spectrum disorder are reported to have atypical sensory processing and deficits in multisensory integration. However, the influence of autistic traits on the formation of such correspondences is relatively unknown. Here, we examined whether autistic traits could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 118 publications
5
37
1
Order By: Relevance
“…Distribution of AQ‐10 scores for the sample of 91 participants is shown in Figure 1. To further understand the effect of autistic traits, participants were divided into three groups as in a previous study (Chen et al., 2021). An AQ score of five was used as the criterion for the high AQ group (AQ ≥ 5; 30 participants), an AQ score of 2 as the criterion for the low AQ group (AQ ≤ 2; 39 participants), and participants with an AQ score between them were grouped into the medium AQ group (3 ≤ AQ ≤ 4; 22 participants).…”
Section: Methodsmentioning
confidence: 99%
“…Distribution of AQ‐10 scores for the sample of 91 participants is shown in Figure 1. To further understand the effect of autistic traits, participants were divided into three groups as in a previous study (Chen et al., 2021). An AQ score of five was used as the criterion for the high AQ group (AQ ≥ 5; 30 participants), an AQ score of 2 as the criterion for the low AQ group (AQ ≤ 2; 39 participants), and participants with an AQ score between them were grouped into the medium AQ group (3 ≤ AQ ≤ 4; 22 participants).…”
Section: Methodsmentioning
confidence: 99%
“…Specially, the white background used in the current study may have enhanced the resemblance to the redcircle in the flag, leading to a strong binding of red and circle (Woods et al, 2016). In a previous study using a questionnaire survey, we observed that people with higher autistic traits showed fewer consensual associations between colors and familiar geometric shapes, which might be explained by a reduced prior knowledge effect in individuals with higher autistic traits (Chen et al, 2021). When testing the strength of CSAs using behavioral experimental methods, those individuals with higher autistic traits showed stronger binding of CSAs.…”
Section: Strength Of Csasmentioning
confidence: 66%
“…For example, the well-known "Bouba-Kiki" effect (i.e., people associate rounded shapes with words like "bouba" or "maluma," and spiky shapes with words like "kiki" or "takete"; Köhler, 1947) was weaker in individuals with ASDs than in controls (Gold & Segal, 2017;Król & Ferenc, 2020;Oberman & Ramachandran, 2008;Occelli et al, 2013). Chen et al (2021) reported that individuals with higher autistic traits showed fewer consensual color-taste (e.g., yellow-sour taste) and CSAs using a questionnaire survey. Hidaka and Yaguchi (2018) found that people with lower autistic traits exhibited a stronger cross-modal congruency effect for brightness-loudness associations in the speeded visual classification task, suggesting that they experienced stronger brightness-loudness associations than did those with higher autistic traits.…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…Previous research has investigated the relations between color and taste/flavor (Spence, 2019;Spence et al, 2015). Specifically, crossmodal correspondences research has revealed that people tend to significantly match particular basic tastes with specific colors (Chen et al, 2021;Motoki, Takahashi, & Spence, 2021;Spence, 2019;Spence et al, 2015;Spence & Levitan, 2021 However, the associations of color with other food-related factors have not been so extensively studied to date. Our findings help to start fill this gap in the experimental literature and reveal that people tend to match nutrients with colors in a way that is somewhat predictable.…”
Section: Contributing To Color Association With Foodrelated Factorsmentioning
confidence: 99%
“…For example, sweet and umami tastes might serve as cues signaling sugar and protein, respectively (e.g., Keast, Costanzo, & Hartley, 2021;Temussi, 2009). Previous research on taste-color correspondences found that umami is associated with the color brown (e.g., Chen et al, 2021; see also Ikeda, 1909Ikeda, /2002. In contrast, our findings on nutrient-color correspondences show that protein is frequently associated with red and orange.…”
Section: Contributing To Color Association With Foodrelated Factorsmentioning
confidence: 99%